Internet of things and ransomware: Evolution, mitigation and prevention - Humayun, Mamoona; Jhanjhi, NZ; Alsayat, Ahmed; Ponnusamy, Vasaki (Egyptian informatics journal, 2021)
Internet of things architecture is the integration of real-world objects and places with the internet. This booming in technology is bringing ease in our lifestyle and making formerly impossible things possible. Internet of things playing a vital role in bridging this gap easily and rapidly. IoT is changing our lifestyle and the way of working the technologies, by bringing them together at the one page in several application areas of daily life. However, IoT has to face several challenges in the form of cyber scams, one of the major challenges IoT has to face is the likelihood of Ransomware attack. Ransomware is a malicious kind of software that restricts access to vital information in some way and demand payment for getting access to this information. The ransomware attack is becoming widespread daily, and it is bringing disastrous consequences, including loss of sensitive data, loss of productivity, data destruction, and loss of reputation and business downtime. Which further leads to millions of dollar daily losses due to the downtime. This is inevitable for organizations to revise their annual cybersecurity goals and need to implement proper resilience and recovery plan to keep business running. However, before proceeding towards providing a practical solution, there is a need to synthesize the existing data and statistics about this crucial attack to make aware to the researchers and practitioners. To fill this gap, this paper provides a comprehensive survey on evolution, prevention and mitigation of Ransomware in IoT context. This paper differs from existing in various dimensions: firstly, it provides deeper insights about Ransomware evolution in IoT. Secondly; it discusses diverse aspects of Ransomware attacks on IoT which include, various types of Ransomware, Current research in Ransomware, Existing techniques to prevent and mitigate Ransomware attacks in IoT along with the ways to deal with an affected machine, the decision about paying the ransom or not, and future emerging trends of Ransomware propagation in IoT. Thirdly, a summary of current research is also provided to show various directions of research. In sum, this detailed survey is expected to be useful for researchers and practitioners who are involved in developing solutions for IoT security.